2022
DOI: 10.1097/jom.0000000000002490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emergency Duties on Cardiovascular Diseases in Firefighters

Abstract: Objectives: This study aimed to examine the effects of firefighters' emergency duties on the incidence of cardiovascular disease (CVD). Methods: We used a 13-year follow-up in a nationwide retrospective cohort study. A total of 363,137 employees were recruited. The sex-and age-specific incidence of CVD (hypertension, angina pectoris, and acutemyocardial infarction [AMI]) in firefighters and public officials was estimated. Results: The overall age-specific sex-based incidence of CVD, except for hypertension, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The authors suggest that prevention and management of occupational exposure in firefighters can reduce the risk of AF and other cardiovascular diseases. Similarly, the article by Jeung et al, (2022) found that firefighters who had engaged in emergency duties were at a higher risk of developing CVD, with the risk increasing with the number of duties performed and being higher for those who had performed emergency duties for 10 or more years. These findings suggest that reducing exposure to emergency duties and managing cardiovascular risk factors may be effective strategies for preventing CVD in firefighters.…”
Section: Cardiac Complicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors suggest that prevention and management of occupational exposure in firefighters can reduce the risk of AF and other cardiovascular diseases. Similarly, the article by Jeung et al, (2022) found that firefighters who had engaged in emergency duties were at a higher risk of developing CVD, with the risk increasing with the number of duties performed and being higher for those who had performed emergency duties for 10 or more years. These findings suggest that reducing exposure to emergency duties and managing cardiovascular risk factors may be effective strategies for preventing CVD in firefighters.…”
Section: Cardiac Complicationsmentioning
confidence: 94%
“…Authors suggest that this may be due to the rigorous physical demands of the firefighting profession, which can accelerate cardiovascular aging and lead to earlier onset of cardiovascular disease. Both studies' results suggest that job-related stress, physical demands, and exposure to toxins may contribute to the development of IHD (Dzikowicz & Carey, 2021) and CVD (Jeung et al, 2022) and implies that career length may be a more important predictor of cardiac effects in firefighters. Risk reduction strategies such as proper screening, management of cardiovascular risk factors, and cardiac rehabilitation may be beneficial, as well as reducing exposure to known risk factors such as smoking and obesity.…”
Section: Cardiac Complicationsmentioning
confidence: 99%
“…The authors suggest that prevention and management of occupational exposure in firefighters can reduce the risk of AF and other cardiovascular diseases. Similarly, the article by Jeung et al, (2022) found that firefighters who had engaged in emergency duties were at a higher risk of developing CVD, with the risk increasing with the number of duties performed and being higher for those who had performed emergency duties for 10 or more years. These findings suggest that reducing exposure to emergency duties and managing cardiovascular risk factors may be effective strategies for preventing CVD in firefighters.…”
Section: Cardiac Complicationsmentioning
confidence: 94%
“…5,6 Previous reports have shown that exposure to occupational-specific stressors (i.e., heat stress, smoke and hazardous chemical exposure, and intense physical demands) increases oxidative stress, inflammation, and vascular dysfunction. 1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19] However, little is known regarding the role of the hypothalamic-pituitary-adrenal (HPA) and sympatheticadreno-medullar (SAM) axes and subsequent physiological stress responses to live fire suppression and CVD risk.…”
mentioning
confidence: 99%
“…The trigger for an adverse cardiac event is multifactorial, as firefighters are exposed to several stressors that induce cardiovascular strain, oxidative stress, and inflammation, which are implicated in the development and progression of CVD 5,6 . Previous reports have shown that exposure to occupational-specific stressors (i.e., heat stress, smoke and hazardous chemical exposure, and intense physical demands) increases oxidative stress, inflammation, and vascular dysfunction 1,2,7–19 . However, little is known regarding the role of the hypothalamic-pituitary-adrenal (HPA) and sympathetic-adreno-medullar (SAM) axes and subsequent physiological stress responses to live fire suppression and CVD risk.…”
mentioning
confidence: 99%